Electrolyte and aluminum-air battery

By adding natural amino acids, sugar compounds and tea tree essential oils to the electrolyte of the aluminum air battery as corrosion inhibitors, the reduction of anode activity and environmental protection caused by inorganic corrosion inhibitors in the existing electrolyte is solved, and the low self-corrosion rate and high electrochemical performance of the aluminum anode are achieved, and the commercial application of aluminum air batteries is promoted.

CN113851665BActive Publication Date: 2025-04-18HUNAN SEIRIOS NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111195997.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-14
Publication Date
2025-04-18
Estimated Expiration
2041-10-14

AI Technical Summary

Technical Problem

Although the inorganic corrosion inhibitor added to the existing aluminum air battery electrolyte can reduce the self-corrosion rate of the aluminum anode, it usually sacrifices the anode activity, and has high preparation cost, environmental pollution and toxic risks, making it difficult to meet the requirements of green and environmental protection.

Method used

A green and environmentally friendly electrolyte is used to add natural amino acids, sugar compounds and plant essential oils (such as tea tree essential oil) to the electrolyte as corrosion inhibitors, and N and O atoms in these organic matter provide a solitary electron pair for aluminum, adsorbing on the aluminum surface, reducing hydrogen evolution self-corrosion.

Benefits of technology

It significantly reduces the self-corrosion rate of the aluminum anode, improves its electrochemical performance, ensures efficient discharge and long life of the aluminum air battery, and meets the requirements of green and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003302972610000081
    Figure BDA0003302972610000081
Patent Text Reader

Abstract

The present invention discloses an electrolyte and an aluminum-air battery, comprising the following raw materials: sodium chloride and a corrosion inhibitor; the corrosion inhibitor comprises the following raw materials: natural amino acids, sugar compounds and plant essential oils. The aluminum-air battery of the present invention uses an electrolyte containing tea tree essential oil, amino acids and sugar compounds, which can control the excessive self-corrosion of the alkaline aluminum-air battery and ensure that the aluminum anode alloy has a high electrochemical activity, which is of great significance for improving the battery discharge efficiency and extending the discharge life, and is conducive to the commercial application of aluminum-air batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to an electrolyte and an aluminum-air battery. Background Art

[0002] Metal-air batteries are a new generation of green batteries. They have low manufacturing costs, high specific energy, recyclable raw materials, and superior performance. Currently, the metal-air batteries that are being studied more include zinc-air batteries, aluminum-air batteries, and lithium-air batteries. The only one that is closest to industrialization is zinc-air batteries. In the potential series, aluminum is more active than zinc and can obtain a higher battery voltage; one aluminum atom can release three electrons, while one zinc atom releases two electrons, so aluminum can increase the energy of the battery; in addition, aluminum reserves are abundant and the price is low, so the research on aluminum-air batteries is progressing very rapidly, and it is a very promising air battery.

[0003] Aluminum-air battery is a new type of battery that uses aluminum and air as battery materials. Aluminum has unique advantages as the anode material of air battery: high electrochemical equivalent, the electrochemical equivalent of aluminum is 2980A·h / kg, the highest metal except lithium; the electrode potential is relatively negative, and its standard electrode potential in alkaline solution is -2.35V (vs.SHE). For anode materials, the more negative the potential, the better, and the battery can provide greater electromotive force; aluminum resources are abundant and the price is low.

[0004] Aluminum-air batteries consist of an aluminum anode, an air cathode, and an electrolyte. During the discharge process, oxygen in the air enters the electrolyte through the air cathode and reaches the reaction interface to undergo a reduction reaction and release electrical energy. The electrolyte is both a "bridge" connecting the air electrode and the aluminum anode, transferring various cations and anions, and a "storage box" that temporarily stores aluminum hydroxide, a product of the discharge process of the aluminum-air battery. Therefore, the performance of the electrolyte of the aluminum-air battery will directly affect the performance of the aluminum-air battery. There are two typical aluminum-air battery electrolytes, alkaline solutions and salt solutions. In order to improve the performance of the electrolyte in the related technology, inorganic corrosion inhibitors are added to the electrolyte; however, although most inorganic corrosion inhibitors can reduce the self-corrosion rate of the aluminum alloy material used in the aluminum anode to a certain extent, they are often at the expense of the activity of the anode; and inorganic corrosive agents are mostly chemically synthesized, with high preparation costs and high prices. Some components may cause environmental pollution and have certain toxic effects on humans, which do not meet environmental protection requirements.

[0005] Therefore, it is necessary to develop an electrolyte that is green and environmentally friendly and can improve the electrochemical performance of aluminum-air batteries. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides an electrolyte, which is green and environmentally friendly and can improve the electrochemical performance of aluminum-air batteries.

[0007] The invention also provides an aluminum-air battery.

[0008] The first aspect of the present invention provides an electrolyte, comprising the following preparation raw materials: sodium chloride and a corrosion inhibitor;

[0009] The corrosion inhibitor comprises the following preparation raw materials: natural amino acid, sugar compound and plant essential oil.

[0010] The corrosion inhibitor of the present invention is added with natural amino acids, sugar compounds and plant essential oils. The organic substances contain a large number of atoms such as N and O, which can provide lone electron pairs for aluminum, so that they are adsorbed on the surface of aluminum, reduce the contact between aluminum and water molecules, and thus reduce hydrogen evolution self-corrosion.

[0011] According to some embodiments of the present invention, the electrolyte includes the following raw materials in mass fractions: 3% to 9% sodium chloride and 0.01% to 1% corrosion inhibitor.

[0012] According to some embodiments of the present invention, the electrolyte comprises 0.01% to 0.8% of corrosion inhibitor in the raw materials for preparation.

[0013] According to some embodiments of the present invention, the corrosion inhibitor comprises the following raw materials in mass fractions: 5% to 10% natural amino acids, 10% to 20% sugar compounds, 20% to 60% plant essential oils and the remainder being solvent.

[0014] According to some embodiments of the invention, the solvent comprises ethanol.

[0015] According to some embodiments of the present invention, the corrosion inhibitor includes the following raw materials in mass fractions: 5% to 10% natural amino acids, 10% to 20% sugar compounds, 20% to 50% plant essential oils and the remainder being solvent.

[0016] According to some embodiments of the present invention, the natural amino acid includes at least one of cysteine, cystine, serine and aspartic acid.

[0017] According to some embodiments of the present invention, the carbohydrate compound includes at least one of glucose, fructose, maltose and sucrose.

[0018] According to some embodiments of the invention, the plant essential oil comprises tea tree essential oil.

[0019] In the corrosion inhibitor of the present invention, tea tree essential oil is extracted from tea tree, has wide sources, low price, and is environmentally friendly and non-toxic; tea tree essential oil is a complex mixture composed of many different types of aromatic compounds, and the main components include: terpinene, pinene, limonene, cineole, terpineol, and cumene. There are lone pairs of electrons in these radical molecules, which can provide electrons to the empty orbits of the metal, and the oxygen atoms in the radicals are adsorbed on the metal surface by the lone pairs of electrons to form an insoluble complex layer, which separates the metal surface from the aqueous solution and plays a corrosion inhibition role. It has the advantages of low cost, low toxicity or non-toxicity, and no environmental pollution. It can significantly reduce the self-corrosion rate of the aluminum anode and improve its electrochemical performance when added to the electrolyte, and has good economic and environmental benefits.

[0020] A second aspect of the present invention provides an aluminum-air battery, the raw materials for preparing which include the above-mentioned electrolyte.

[0021] According to some embodiments of the present invention, the aluminum-air battery further includes an aluminum anode and an air cathode.

[0022] According to some embodiments of the present invention, the aluminum anode is composed of the following raw materials in weight fractions: 0.05% to 1% Mg, 0.05% to 4% Ga, 0.01% to 2% In, and the balance is Al.

[0023] Mg element is beneficial to reduce the anodic polarization of aluminum anode dissolution and increase the current density of aluminum anode, but Mg easily reacts with Al to form an intermediate product Mg5Al with cathode characteristics. 18 , resulting in intergranular corrosion and reducing the utilization rate of aluminum anode.

[0024] The Ga element can prevent the formation of a passivation film on the aluminum surface and change the anisotropy of aluminum grains during the dissolution process, thereby making the aluminum anode corrode evenly and improving the electrochemical performance.

[0025] The addition of In element is easy to produce segregation phase, forming activation sites, promoting the dissolution of the surrounding aluminum matrix, and at the same time, the In dissolved in the solution 3+ Deposition on the surface of the aluminum substrate separates the aluminum substrate and the oxide film, which is beneficial to the activation of the anode, but it is easy to reduce the utilization rate of the aluminum anode. Therefore, one or more of Mg, Ga and In are added to the aluminum anode, and the mutual balance between the elements is used to make the aluminum anode effectively inhibit hydrogen self-corrosion and facilitate the conversion of active substances.

[0026] According to some embodiments of the present invention, the air cathode is formed by pressing a catalyst layer, a conductive nickel mesh and a waterproof and breathable layer.

[0027] According to some embodiments of the present invention, the thickness of the air cathode is 0.2 mm to 0.6 mm.

[0028] According to some embodiments of the present invention, raw materials for preparing the catalytic layer include: a catalyst, a conductive agent, activated carbon and a binder.

[0029] According to some embodiments of the present invention, the catalyst is γ-MnO2.

[0030] According to some embodiments of the present invention, the conductive agent includes at least one of carbon black, graphene, metal powder and conductive polymer.

[0031] According to some embodiments of the present invention, the adhesive includes at least one of polytetrafluoroethylene, polyvinylidene fluoride and polyvinyl alcohol.

[0032] According to some embodiments of the present invention, the catalytic layer includes the following raw materials in parts by weight: 10 to 40 parts of catalyst, 5 to 20 parts of conductive agent, 25 to 65 parts of activated carbon and 20 to 55 parts of adhesive.

[0033] According to some embodiments of the present invention, the thickness of the catalytic layer is 0.3 mm to 0.8 mm.

[0034] According to some embodiments of the present invention, the waterproof and breathable layer is composed of the following raw materials: polytetrafluoroethylene and acetylene black.

[0035] According to some embodiments of the present invention, the mass fraction of polytetrafluoroethylene in the waterproof and breathable layer is 40% to 60%.

[0036] According to some embodiments of the present invention, the waterproof and breathable layer has a thickness of 0.3 mm to 0.8 mm.

[0037] According to at least one embodiment of the present invention, the following beneficial effects are achieved:

[0038] The aluminum-air battery of the present invention adopts an electrolyte containing tea tree essential oil, amino acids and sugar compounds, which can control the excessive self-corrosion of the alkaline aluminum-air battery and ensure that the aluminum anode alloy has high electrochemical activity, which is of great significance for improving the battery discharge efficiency and extending the discharge life, and is conducive to the commercial application of aluminum-air batteries; the open circuit voltage of the aluminum alloy anode material is good, which is -1.86 (vs. SHE) to -1.98 V (vs. SHE), and the self-corrosion rate in the electrolyte is low (≤3.58 mg / cm 2 h), the surface corrosion is uniform; the aluminum-air battery has a discharge current density of 100mA / cm 2 The electromotive force after 10 hours of testing is 1.90V~2.15V, which has excellent electrochemical performance. DETAILED DESCRIPTION

[0039] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0040] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0041] The specific embodiments of the present invention are described in detail below. DETAILED DESCRIPTION

[0043] The present invention will be further described below in conjunction with specific implementation modes.

[0044] Example 1

[0045] The electrolyte of this embodiment is composed of the following raw materials in percentage by mass: 6% sodium chloride, 0.5% corrosion inhibitor and the balance water.

[0046] The corrosion inhibitor of this embodiment is composed of the following raw materials in mass fraction: 10% natural amino acid (cysteine), 15% sugar compound (glucose), 60% plant essential oil (tea tree essential oil, CAS No.: 68647-73-4) and the balance is ethanol.

[0047] The preparation method of the electrolyte is: adding sodium chloride into water to obtain a sodium chloride solution; and then adding a corrosion inhibitor into the sodium chloride solution to obtain the electrolyte.

[0048] The aluminum-air battery of this embodiment includes an aluminum anode, an air cathode and an electrolyte, and the electrolyte is the electrolyte for the aluminum-air battery mentioned above.

[0049] The aluminum anode is an aluminum alloy anode material, and is composed of the following components in weight percentage: Mg 0.6%, In 0.1%, Ga 0.05% and the balance is Al.

[0050] The air cathode is formed by pressing a catalytic layer, a conductive nickel mesh and a waterproof and breathable layer;

[0051] The catalytic layer is a 0.6mm thick film layer made by rolling and mixing γ-MnO2, carbon black, activated carbon and polytetrafluoroethylene in a mass ratio of 1:1:4:5;

[0052] The waterproof and breathable layer is a film layer with a thickness of 0.4 mm made by rolling and mixing polytetrafluoroethylene and acetylene black in a weight ratio of 1:1;

[0053] Finally, the catalytic layer, the conductive nickel mesh and the waterproof and breathable layer were pressed into an air cathode with a thickness of 0.3 mm.

[0054] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 3.24 mg / cm 2 h, the open circuit potential is -1.92 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 1.98V, and the surface of the anode alloy is corroded evenly.

[0055] Example 2

[0056] The difference between this embodiment and embodiment 1 is that:

[0057] The electrolyte of this embodiment is composed of the following raw materials in percentage by mass: 6% sodium chloride, 1% corrosion inhibitor and the balance water.

[0058] The corrosion inhibitor of this embodiment is composed of the following raw materials in mass fraction: 10% natural amino acid (cystine), 20% sugar compound (maltose), 60% plant essential oil (tea tree essential oil) and the balance is ethanol.

[0059] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 2.17 mg / cm 2 h, the open circuit potential is -1.95 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 2.15V, and the surface of the anode alloy is corroded evenly.

[0060] Example 3

[0061] The difference between this embodiment and embodiment 1 is that:

[0062] The electrolyte of this embodiment is composed of the following raw materials in the following mass fractions: 9% sodium chloride, 1% corrosion inhibitor and the balance water.

[0063] The corrosion inhibitor of this embodiment includes the following raw materials in mass fractions: 5% natural amino acid (cystine), 10% sugar compound (fructose), 20% plant essential oil (tea tree essential oil) and the balance ethanol.

[0064] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 3.58 mg / cm 2 h, the open circuit potential is -1.86 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 1.90V, and the surface of the anode alloy is corroded evenly.

[0065] Example 4

[0066] The difference between this embodiment and embodiment 1 is that:

[0067] The electrolyte of this embodiment is composed of the following raw materials in percentage by mass: 3% sodium chloride, 0.5% corrosion inhibitor and the balance water.

[0068] The corrosion inhibitor of this embodiment includes the following raw materials in mass fractions: 8% natural amino acid (cysteine), 20% sugar compound (glucose), 50% plant essential oil (tea tree essential oil) and the balance ethanol.

[0069] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 2.93 mg / cm 2 h, the open circuit potential is -1.98 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 2.08V, and the surface of the anode alloy is corroded evenly.

[0070] Example 5

[0071] The difference between this embodiment and embodiment 1 is that:

[0072] The electrolyte of this embodiment is composed of the following raw materials in percentage by mass: 5% sodium chloride, 0.8% corrosion inhibitor and the balance water.

[0073] The corrosion inhibitor of this embodiment includes the following raw materials in mass fractions: 8% natural amino acid (cysteine), 20% sugar compound (glucose), 50% plant essential oil (tea tree essential oil) and the balance ethanol.

[0074] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 2.85 mg / cm 2 h, the open circuit potential is -1.93 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm2 The electromotive force after testing for 10 hours is 2.10V, and the surface of the anode alloy is corroded evenly.

[0075] Example 6

[0076] The difference between this embodiment and embodiment 1 is that:

[0077] The electrolyte of this embodiment is composed of the following raw materials in percentage by mass: 7% sodium chloride, 0.6% corrosion inhibitor and the balance water.

[0078] The corrosion inhibitor of this embodiment includes the following raw materials in mass fractions: 8% natural amino acid (cysteine), 20% sugar compound (glucose), 50% plant essential oil (tea tree essential oil) and the balance ethanol.

[0079] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 3.02 mg / cm 2 h, the open circuit potential is -1.95 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after testing for 10 hours is 2.01V, and the surface of the anode alloy is corroded evenly.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that:

[0082] The electrolyte of this embodiment is composed of the following raw materials in percentage by mass: 8% sodium chloride, 0.7% corrosion inhibitor and the balance water.

[0083] The corrosion inhibitor of this embodiment includes the following raw materials in mass fractions: 8% natural amino acid (cysteine), 20% sugar compound (glucose), 50% plant essential oil (tea tree essential oil) and the balance ethanol.

[0084] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 3.46 mg / cm 2 h, the open circuit potential is -1.91 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 1.96V, and the surface of the anode alloy is corroded evenly.

[0085] Comparative Example 1

[0086] The difference between this comparative example and Example 1 is that cysteine ​​is not added.

[0087] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 5.06 mg / cm 2h, the open circuit potential is -1.85V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100mA / cm 2 The electromotive force after 10 hours of testing is 1.86V, and the surface of the anode alloy is corroded evenly.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that no glucose is added.

[0090] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 4.96 mg / cm 2 h, the open circuit potential is -1.82 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 1.88V, and the surface of the anode alloy is corroded evenly.

[0091] Comparative Example 3

[0092] The difference between this embodiment and embodiment 1 is that tea tree essential oil is not added.

[0093] The self-corrosion rate of the aluminum alloy anode in the electrolyte of this embodiment is 6.06 mg / cm 2 h, the open circuit potential is -1.77 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2 The electromotive force after 10 hours of testing is 1.76V, and the surface of the anode alloy is corroded evenly.

[0094] The test results of the electrolyte performances prepared in Examples 1 to 7 of the present invention and Comparative Examples 1 to 3 are shown in Table 1.

[0095]

[0096]

[0097] From the data in Table 1, we know that:

[0098] The self-corrosion rate in the electrolyte obtained in Examples 1 to 7 of the present invention is as low as 2.17 mg / cm 2 ·h~3.58mg / cm 2 h, the open circuit potential reaches -1.86 (vs. SHE) ~ -1.98 V (vs. SHE), and the discharge current density of the composed air battery in the electrolyte is 100 mA / cm 2The electromotive force of the test for 10 hours is 1.90V-2.15V, and the surface of the anode alloy corrodes evenly. The experimental results show that the electrolyte of the present invention can significantly reduce the self-corrosion rate of the aluminum anode, so that the aluminum anode alloy has good corrosion resistance and high electrochemical activity, meeting the requirements of high current density discharge of alkaline aluminum-air batteries.

[0099] In summary, the aluminum-air battery of the present invention adopts an electrolyte containing tea tree essential oil, amino acids and sugar compounds, which can not only control the excessive self-corrosion of the alkaline aluminum-air battery, but also ensure that the aluminum anode alloy has a high electrochemical activity, which is of great significance for improving the battery discharge efficiency and extending the discharge life, and is conducive to the commercial application of aluminum-air batteries; the open circuit voltage of the aluminum alloy anode material is good, which is -1.86 (vs. SHE) ~ -1.98V (vs. SHE), and the self-corrosion rate in the electrolyte is low (≤3.58mg / cm 2 h), the surface corrosion is uniform; the aluminum-air battery has a discharge current density of 100mA / cm 2 The electromotive force after 10 hours of testing is 1.90V~2.15V, which has excellent electrochemical performance.

[0100] The embodiments of the present invention are described in detail above in conjunction with specific implementation methods, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. An aluminum-air battery comprising an electrolyte, an aluminum anode and an air cathode, characterized in that: The electrolyte is composed of the following raw materials in mass fractions: 3% to 9% sodium chloride and 0.01% to 1% corrosion inhibitor, and the balance is water; The corrosion inhibitor is composed of the following raw materials in mass fraction: 5% to 10% natural amino acids, 10% to 20% sugar compounds, 20% to 60% plant essential oils and the balance is solvent; the natural amino acids include at least one of cysteine, cystine, serine and aspartic acid; the sugar compounds include at least one of glucose, fructose, maltose and sucrose; the plant essential oils include tea tree essential oil; The aluminum anode is composed of the following raw materials in weight fractions: 0.05% to 1% Mg, 0.05% to 4% Ga, 0.01% to 2% In and the balance Al.

2. The aluminum-air battery according to claim 1, characterized in that: The electrolyte comprises 0.01% to 0.8% of corrosion inhibitor in its preparation raw materials.

3. The aluminum-air battery according to claim 1, characterized in that: The corrosion inhibitor is composed of the following raw materials in mass fraction: 5% to 10% of natural amino acid, 10% to 20% of sugar compound, 20% to 50% of plant essential oil and the balance is solvent.

4. The aluminum-air battery according to claim 1, characterized in that: The air cathode is formed by pressing a catalyst layer, a conductive nickel mesh and a waterproof and breathable layer.

5. An aluminum-air battery according to claim 4, characterized in that: The thickness of the air cathode is 0.2 mm to 0.6 mm.

6. The aluminum-air battery according to claim 4, characterized in that: The raw materials for preparing the catalytic layer include: catalyst, conductive agent, activated carbon and adhesive.

7. An aluminum-air battery according to claim 6, characterized in that: The catalyst is γ-MnO2.

8. The aluminum-air battery according to claim 6, characterized in that: The conductive agent includes at least one of carbon black, graphene, metal powder and conductive polymer.

9. The aluminum-air battery according to claim 6, characterized in that: The adhesive includes at least one of polytetrafluoroethylene, polyvinylidene fluoride and polyvinyl alcohol.

10. The aluminum-air battery according to claim 6, characterized in that: The catalytic layer comprises the following raw materials in parts by weight: 10 to 40 parts of catalyst, 5 to 20 parts of conductive agent, 25 to 65 parts of activated carbon and 20 to 55 parts of adhesive.

11. The aluminum-air battery according to claim 6, characterized in that: The thickness of the catalytic layer is 0.3 mm to 0.8 mm.

12. The aluminum-air battery according to claim 4, characterized in that: The waterproof and breathable layer is composed of the following raw materials: polytetrafluoroethylene and acetylene black.

13. An aluminum-air battery according to claim 12, characterized in that: The mass fraction of polytetrafluoroethylene in the waterproof and breathable layer is 40% to 60%.

14. The aluminum-air battery according to claim 12, characterized in that: The thickness of the waterproof and breathable layer is 0.3 mm to 0.8 mm.

Citation Information

Patent Citations

  • Electrolyte corrosion inhibitor, electrolyte for aluminum air cell and aluminum air cell

    CN105140595A

  • Electrolyte corrosion inhibitor, aluminum-air battery electrolyte and preparation method of aluminum-air battery electrolyte

    CN105870545A

  • Aluminum-air battery electrolyte, aluminum-air battery and manufacturing method thereof

    CN107275720A